Fatigue damage of turbine shafts of sugar plants at asynchronous connections of turbogenerator to the power network - Kuyevda, Valery; Bovsunovskyy, Anatoly; Kuievda, Yulia; Shtefan, Yevgenii (My University, 2013)
The increase of durability of power equipment of sugar plants is the actual problem. One of the important component part of this problem is the torsional vibration of turbine shafts caused by the action of the reactive electromagnet moments which arise at asynchronous connections of turbogenerator to the power network. In some cases the torsional vibration of turbine shafts leads to theirs essential fatigue damage. The calculations of fatigue damage of most strained parts of the turbine shaft at forced torsional vibration were executed with the ANSYS software (modal analysis).
Keywords: turbine; fatigue damage; asynchronous connections; турбіна; втомне пошкодження; несинхронне включення; турбина; усталостное повреждение; несинхронное включение; кафедра електропостачання і енергоменеджменту; кафедра машин і апаратів харчових та фармацевтичних виробництв